Sleep Disruption in Chronic Rhinosinusitis: Risk Factors Predictive of Worse Sleep Quality - Hui, Jessica W.; Gunawan, Ferry; Ong, Jason; Burgess, Helen J.; Sarrafi, Shahram; Herdegen, James J.; Codispoti, Christopher D.; Tobin, Mary C.; Schleimer, Robert P.; Batra, Pete S.; LoSavio, Phillip S.; Keshavarzian, Ali; et al. (Journal of allergy and clinical immunology, 2017)
Patient charts were reviewed for CRS characteristics, including nasal polyps, histopathology of the sinus tissue (neutrophilic inflammation, eosinophilic inflammation, fibrosis, edema, basement membrane thickening), Lund-Mackay Score (LMS) which is a radiographic score of CRS severity, and comorbid diseases (asthma, AERD, allergic rhinitis, GERD).